Neuroimaging of mild behavioral impairment: A systematic review. Issue 1 (13th February 2023) - Matsuoka, Teruyuki; Imai, Ayu; Narumoto, Jin
Abstract: There are many neuroimaging studies of mild behavioral impairment (MBI), but the results have been somewhat inconsistent. Moreover, it remains unclear whether MBI is a risk factor or prodromal symptom of dementia. Therefore, a systematic review was conducted to summarize the results of neuroimaging studies of MBI and consider whether MBI is a prodromal symptom of dementia in terms of its neural correlates. A systematic review supported by a JSPS Grant‐in‐Aid for Scientific Research (C) was conducted using MBI neuroimaging studies identified using PubMed, PsycINFO, CINAHL, and Google Scholar on November 1, 2022. The inclusion criteria were (i) neuroimaging study; (ii) research on human subjects; (iii) papers written in English; and (iv) not a case study, review, book, comments, or abstract only. Joanna Briggs Institute critical appraisal checklists were used to assess the quality of selected studies, and 23 structural and functional imaging studies were ultimately included in the systematic review. The structural studies suggested an association of MBI with atrophy in the hippocampus, parahippocampal gyrus, entorhinal cortex, and temporal lobe, whereas the functional studies indicated involvement of an altered default mode network, frontoparietal control network, and salience network in MBI. A limitation in many studies was the use of region‐of‐interest analysis. The brain areas detected as neural correlates of MBI are considered to be alterations in the early stage of each dementia. Therefore, MBI may emerge against a background of pathological changes in dementia. Abstract : The brain areas detected as neural correlates of MBI are considered to be alterations in the early stage of each dementia. Therefore, MBI may emerge against a background of pathological changes in dementia. Each brain region may also be linked to conversion from MBI to each dementia.